193k views
4 votes

10 - 3 √(1.21)

User Randomx
by
5.1k points

1 Answer

4 votes

The given expression is:


10-3√(1.21)

Now, we know that the square of 1.1 is 1.21, which means that 1.1 multiplied by itself gives 1.21.

Mathematically, that can be expressed as:


1.1* 1.1=1.21

or,
(1.1)^2=1.21

thus, the square root of 1.21 is 1.1

or
√(1.21)=1.1

Thus, applying this in the expression in the question given to us, we will get:


10-3√(1.21)=10-3* 1.1=10-3.3=6.7

Thus, 6.7 is the final answer for the given expression.

User Kevin Glier
by
5.5k points